13m+6n-4m+11n=

Simple and best practice solution for 13m+6n-4m+11n= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13m+6n-4m+11n= equation:


Simplifying
13m + 6n + -4m + 11n = 0

Reorder the terms:
13m + -4m + 6n + 11n = 0

Combine like terms: 13m + -4m = 9m
9m + 6n + 11n = 0

Combine like terms: 6n + 11n = 17n
9m + 17n = 0

Solving
9m + 17n = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-17n' to each side of the equation.
9m + 17n + -17n = 0 + -17n

Combine like terms: 17n + -17n = 0
9m + 0 = 0 + -17n
9m = 0 + -17n
Remove the zero:
9m = -17n

Divide each side by '9'.
m = -1.888888889n

Simplifying
m = -1.888888889n

 

See similar equations:

| 3y+4w= | | X-5+53+72=180 | | 3m+4m=63 | | x-5+x-10=10 | | x^2-8x-52=0 | | 8(x-2)-8(x-6)=(x-6)(x-2) | | Y=x^2+4x-7 | | 4z+5z=(4+5)z | | 0.3(24p-66)=3p+43 | | X^4+2x^3-21=8 | | x^2=-11x-10 | | 3x^2=6x-1 | | x^2+x^2+14x+49=169 | | 5x^4-20x^2=0 | | 3x^3+2x^2=12x+8 | | 9y^3+8=4y+18y^2 | | 4x^2+44x=48 | | 4x+3=9+2x | | v-3a=44 | | 4(3x+5)+2=10 | | a=.5*b*8 | | 3x^2-7x-5=0 | | 18=1.8c | | 0=12x^2+29x+17 | | 5=6 | | 5=1003x | | 5=3(2x+5) | | 4.7x+3.2y=12.9 | | X^3=-216 | | 8+2x-x^2=6x^3 | | X^3+2x^2+5x+10=0 | | 13m+5n-3m+9n= | | 1.5x+6=18 | | -2m-3=9 | | 2(12-8x)=1x-11x | | 2y=5x-4 | | 3x-4=2x-16 | | 5*5*5*5*5=35 | | 81=2n-15 | | 112=-9a+4 | | -3(x+7)=4 | | y=x^3 | | 9x-34=-2(x+6) | | 22=4w+7 | | 2-2d=-75 | | x+17=28 | | (4x-7).2=9.4 | | 7n+n=32 | | .5*5= | | Y=15 | | 11r-2=-24 | | x+14-8x=-7 | | r^2-8r+16=0 | | 2.4=2.6y-5.9y-0.9 | | 2x^4+x^3-8x^2-x+6=0 | | (3x-85)=4x | | 4x+6x+2=0 | | 14m+3=-1 | | y=3x^2-147 | | -15x+55=3x+6 | | (y-5)=3(x+2) | | (11+3x)-5=(6+3x) | | 56=.20x | | 14x^2-x-3=0 | | 380=18x |